Brief Warm and Aldo-Keto Reductase Family AspiAKR1B1 Contribute to Cold Adaptation of Aleurocanthus spiniferus - Zhi-Fei Jia; Yan-Ge Cui; Meng-Yuan Liu; Jeremiah Joe Kabissa; Yong-Yu Xu; Zhi-Wei Kang; Zhen-Zhen Chen (Insects)
Aleurocanthus spiniferus not only damages plant leaves directly but also causes a sooty blotch due to the honeydew secreted by the nymphs and adults. This pest is widespread and seems to be spreading from low latitude to higher latitude areas where winters are typically colder, indicating an increase in its cold tolerance. Changes in temperature help insects to anticipate the arrival of winter, allowing them to take defensive measures in advance. This study examines the impacts of brief warm pulses on the low-temperature tolerance of A. spiniferus, and analyzes the physiological and biochemical mechanisms underlying its cold adaptation, utilizing seasonal differences in cold tolerance. Intermittent training at 25 °C significantly improved the survival rate of overwintering nymphs (third and fourth instar) at −7 °C. Analysis of seasonal differences in the supercooling point (SCP) and freezing point (FP) revealed that overwintering nymph had the highest cold tolerance in November. Seasonal variation in levels of cold-resistant substances were also observed, with moisture decreasing during overwintering, while fat and glycerol levels increased. Conversely, glucose, sorbitol, and trehalose levels rose significantly at the end of the overwintering period. The expression profile of cold-resistant genes indicated that the aldo-keto reductase family 1 member B1 in Aleurocanthus spiniferus (AspiAKR1B1) shows a significant decrease at the end of the overwintering period. Knocking down AspiAKR1B1 led to a marked reduction in the cold tolerance of A. spiniferus. Therefore, brief warm pulses and AspiAKR1B1 are key factors contributing to the enhanced cold tolerance of A. spiniferus. This research provides theoretical support for preventing the further spread of A. spiniferus to higher latitudes, and offers technical guidance for developing effective pest control measures.